2021
DOI: 10.1128/jcm.02596-20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 16 Serological SARS-CoV-2 Immunoassays in 16 Clinical Laboratories

Abstract: Serological SARS-CoV-2 assays are needed to support clinical diagnosis and epidemiological investigations. Recently, assays for large-scale detection of total antibodies (total-Ab) and immunoglobulin (Ig) G and M against SARS-CoV-2 antigens have been developed, but there are limited data on the diagnostic accuracy of these assays. This study was a Danish national collaboration and evaluated fifteen commercial and one in-house anti-SARS-CoV-2 assays in sixteen laboratories. Sensitivity was evaluated using 150 s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
99
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 28 publications
17
99
1
Order By: Relevance
“…In contrast to sensitivity, the specificities of LFA and ECLIA were very high in this study. These results were consistent with those of previous studies using the same kits [1014]. Although there were no samples with false-positive results for LFA-detected anti-SARS-CoV-2 IgM antibodies and ECLIA-detected total antibodies, there were two samples with false-positive results for LFA-detected SARS-CoV-2 IgG antibodies.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast to sensitivity, the specificities of LFA and ECLIA were very high in this study. These results were consistent with those of previous studies using the same kits [1014]. Although there were no samples with false-positive results for LFA-detected anti-SARS-CoV-2 IgM antibodies and ECLIA-detected total antibodies, there were two samples with false-positive results for LFA-detected SARS-CoV-2 IgG antibodies.…”
Section: Discussionsupporting
confidence: 92%
“…[9] ECLIA’s sensitivity for anti-SARS-CoV-2 total antibodies was 0.783 in this study, which was higher than that of LFA. However, ECLIA’s sensitivity in this study was lower than that reported in previous studies using the same ECLIA kit; the sensitivity in previous studies was 0.920–0.995 [1012]. One study reported that ECLIA’s sensitivity in all patients was 0.920–0.927; however, ECLIA’s sensitivity in 6 (4.0%) asymptomatic patients and 37 (24.8%) mild patients was reported to be approximately 0.800.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations